2019
DOI: 10.1101/583104
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population history from the Neolithic to present on the Mediterranean island of Sardinia: An ancient DNA perspective

Abstract: 34Recent ancient DNA studies of western Eurasia have revealed a dynamic history of admixture, 35 with evidence for major migrations during the Neolithic and Bronze Age. The population of the 36 Mediterranean island of Sardinia has been notable in these studies -Neolithic individuals from 37 mainland Europe cluster more closely with Sardinian individuals than with all other present-day 38 Europeans. The current model to explain this result is that Sardinia received an initial influx 39 of Neolithic anc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…An ancient DNA study of Sardinia that appears alongside this one concurs that modern Sardinians harbor large proportions of ancestry from early Sardinian farmers as well as significant contributions from later periods that are larger than previously estimated. That second study also agrees with our finding that many coastal Sardinian sites harbored people with little ancestry from earlier local Sardinians in the Iron Age and antiquity 85 .…”
Section: Resultssupporting
confidence: 91%
“…An ancient DNA study of Sardinia that appears alongside this one concurs that modern Sardinians harbor large proportions of ancestry from early Sardinian farmers as well as significant contributions from later periods that are larger than previously estimated. That second study also agrees with our finding that many coastal Sardinian sites harbored people with little ancestry from earlier local Sardinians in the Iron Age and antiquity 85 .…”
Section: Resultssupporting
confidence: 91%
“…Therefore, it cannot be excluded, that these females also originate from regions further south since also some regions e.g., Italy are not genetically described so far for this particular time span. However, individuals without any steppe-related ancestry can be found up until 2479-1945 BCE for example in Iberia or until 2900-1700 BCE in the Minoan population of Crete 21,36 and even later on Sardinia where steppe-related ancestry arrives around 300 CE 37 and where studies of present-day Sardinians found indications of continuity in mountainous regions since Neolithic times 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Then the membrane was washed two times with 720 μl of the commercial PE buffer form Qiagen, and then the DNA was eluted in 100 μl TET buffer (1 mM EDTA, 10 mM Tris-HCl, 0.05 % Tween-20, ref. 38 ). Sequencing libraries were prepared after 39 .…”
Section: Methodsmentioning
confidence: 99%
“…The recent and detailed reconstruction of the phylogeny of this haplogroup [56] has revealed that the rare European R1b-V88 lineages (R1b-M18 and R1b-V35) originated from the root of the phylogeny much earlier (about 12.34 kya) than the separation of the African lineages (7.85 ± 0.90 kya), thus supporting an origin of R1b-V88 outside Africa and a subsequent diffusion in sub-Saharan Africa through the Last Green Sahara period during the Middle-Holocene [56]. Interestingly, recent studies on ancient DNA [60,61,62] identified the most ancient R1b-V88 samples (dated 11 and 9 ky) in East Europe (Serbia and Ukraine, respectively) and more recent R1b-V88 samples (dated 7 and 6 ky) in Spain (I0410) and Germany (I1593, I0559) thus supporting a European origin and opening new grounds for discussion concerning the routes towards Africa and Sardinia, where R1b-V88 characterizes a considerable number of ancient specimens [62,63].…”
Section: Resultsmentioning
confidence: 96%